2007
DOI: 10.1002/dvdy.21243
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pinin in neural crest, dorsal dermis, and axial skeleton development and its involvement in the regulation of Tcf/Lef activity in mice

Abstract: Previous in vitro studies have indicated multiple and varied roles of Pinin (PNN); however, its in vivo role has remained unclear. Here, we report generation of null, hypomorphic, and conditional Pnn alleles in mice. We found that insertion of neomycin-resistance cassette into intron 8 of Pnn resulted in knockdown of Pnn, which allowed Pnn hypomorphic embryos to pass peri-implantation lethality. These mice are lethal at perinatal stages and exhibit defects in the cardiac outflow tract, palate, dorsal dermis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 51 publications
(80 reference statements)
1
33
0
Order By: Relevance
“…28,2008 CtBP (21). Splicing assays were performed using RT-PCR, where unspliced message was detected using primers against E-cadherin intron 2, whereas total spliced E-cadherin message was detected using primers spanning the region between exons 4 and 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…28,2008 CtBP (21). Splicing assays were performed using RT-PCR, where unspliced message was detected using primers against E-cadherin intron 2, whereas total spliced E-cadherin message was detected using primers spanning the region between exons 4 and 8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted disruption of Sfrs10 (Mende et al, 2010), SRp20, SRSF2 (also known as SC35), and SRSF1 (also known as ASF/ SF2) resulted in early embryonic lethality (Moroy and Heyd, 2007). Recently, using a tissue-specific mouse model with deletion of exons 3-8 in pnn gene, investigators showed that Pnn plays important roles in development of the heart, cornea, and intestine (Joo et al, 2007;Joo et al, 2010a;Joo et al, 2010b). Although all of these loss-of-function mouse models demonstrated that SR proteins are important for embryonic development, the underlying mechanism relating loss of SR protein expression to embryonic lethality or cellular apoptosis has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…They are then guided to their destinations and differentiate into mature structures. Hypomorphic reduction of pnn resulted in a wide range of developmental defects in mice (Joo et al 2007). Disorganized dorsal dermis devoid of brown adipose tissue, and malformation of axial skeleton in pnn hypomorphic mice suggested that pnn is important for the development of these somite derivatives.…”
Section: Introductionmentioning
confidence: 97%
“…Disorganized dorsal dermis devoid of brown adipose tissue, and malformation of axial skeleton in pnn hypomorphic mice suggested that pnn is important for the development of these somite derivatives. In addition, defects in the cleft palate, cardiac outflow tract and craniofacial skeleton indicated that pnn also has an essential role in neural crest development (Joo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation